The Political Thoughts of Al-Farabi and Al-Mawardi - Aditya Nanda Saputra; Muhammad Daini; Muhammad Syahrul; Zulfian Achmad Noviandi; Surya Sukti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze and compare the political thought of Al-Farabi and Al-Mawardi in the classical Islamic political tradition. The main problem in this study is the gap between philosophical-idealistic and normative-practical approaches that are often studied separately. This research uses a qualitative method with a literature approach through the study of the main works of the two figures and SINTA-indexed journal articles. The results of the study show that Al-Farabi emphasizes the concept of an ideal state (al-Madinah al-Fadhilah) that is oriented towards shared happiness through moral and intellectual leadership. Meanwhile, Al-Mawardi emphasized the practical aspects of government through the concept of the caliphate which includes the requirements of leaders and institutional systems. These two thoughts complement each other in understanding Islamic politics ideally and practically. This research confirms the relevance of the two thoughts in answering contemporary political challenges.